2008
DOI: 10.1590/s0100-879x2008000900008
|View full text |Cite
|
Sign up to set email alerts
|

Lead reduces tension development and the myosin ATPase activity of the rat right ventricular myocardium

Abstract: Lead (Pb 2+ ) poisoning causes hypertension, but little is known regarding its acute effects on cardiac contractility. To evaluate these effects, force was measured in right ventricular strips that were contracting isometrically in 45 male Wistar rats (250-300 g) before and after the addition of increasing concentrations of lead acetate (3,7,10,30, 70, 100, and 300 µM) to the bath. Changes in rate of stimulation (0.1-1.5 Hz), relative potentiation after pauses of 15, 30, and 60 s, effect of Ca 2+ concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…To ensure that the effects were not dependent on time, another group of rats was used under the same conditions in a time control experiment performed 1 h later, after iv administration of 0.9% saline. This lead concentration was selected because it is known to produce a clear negative inotropic effect and to reduce myosin ATPase activity in the rat myocardium (23).…”
Section: Isolated Rat Tail Vascular Bed Preparationmentioning
confidence: 99%
“…To ensure that the effects were not dependent on time, another group of rats was used under the same conditions in a time control experiment performed 1 h later, after iv administration of 0.9% saline. This lead concentration was selected because it is known to produce a clear negative inotropic effect and to reduce myosin ATPase activity in the rat myocardium (23).…”
Section: Isolated Rat Tail Vascular Bed Preparationmentioning
confidence: 99%
“…However, other reports have indicated that acute lead administration (30 µM in the bath) to perfused rat hearts attenuates positive inotropic responses 15. In rat papillary muscles, acute 100 µM lead in the bath, although not affecting sarcoplasmic reticulum activity, has a negative inotropic effect and reduces myosin ATPase activity 17. Lead action contributing to calcium channel blocking has also been reported in rat myocytes and Xenopus laevis oocytes 16.…”
Section: Discussionmentioning
confidence: 96%
“…The first contraction after rest was taken as an index of sarcolemmal calcium influx 18. Taking into account that the rat myocardium saturates its positive inotropic response at extracellular Ca 2+ concentrations lower than those for other species 17, the protocols using isoproterenol were performed with reduced extracellular Ca 2+ concentrations (0.62 mM). In the last protocol, tetanic tension was elicited before (control condition - time 0) and at 15, 30, 45, 60, and 90 min after lead administration by high frequency stimulation (10 Hz for 15 s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…*P \ 0.05 when compared to the same parameter versus control group. All comparisons were performed using an unpaired Student's t test isolated rat cardiac muscles exposed to 8 lM lead acetate exhibited increased contractility [64], but 30-100 lM lead decreased force by reducing calcium influx and myosin ATPase activity [65]. Nevertheless, by using a chronic model of lead exposure in the rat, Fioresi et al [3] demonstrated that despite no change in the contractile force of isolated cardiac muscle, there was strong evidence of impaired sarcoplasmic reticulum (SR) function.…”
Section: Cardiovasc Toxicolmentioning
confidence: 99%